2021
DOI: 10.3390/brainsci11081055
|View full text |Cite
|
Sign up to set email alerts
|

Brain Image Segmentation in Recent Years: A Narrative Review

Abstract: Brain image segmentation is one of the most time-consuming and challenging procedures in a clinical environment. Recently, a drastic increase in the number of brain disorders has been noted. This has indirectly led to an increased demand for automated brain segmentation solutions to assist medical experts in early diagnosis and treatment interventions. This paper aims to present a critical review of the recent trend in segmentation and classification methods for brain magnetic resonance images. Various segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 66 publications
(140 reference statements)
0
32
0
1
Order By: Relevance
“…3D reconstruction has diverse applications in the medical field like complex intracranial structures (10) , craniofacial abnormalities (11) , microcalcifications in breast cancer (12) , artery visualization for cardiac applications (13) . Reconstruction of the tumor with its boundary completely depends on the accurate extraction of the irregularly shaped tumor from the corresponding MR images.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D reconstruction has diverse applications in the medical field like complex intracranial structures (10) , craniofacial abnormalities (11) , microcalcifications in breast cancer (12) , artery visualization for cardiac applications (13) . Reconstruction of the tumor with its boundary completely depends on the accurate extraction of the irregularly shaped tumor from the corresponding MR images.…”
Section: Methodsmentioning
confidence: 99%
“…Accuracy can be estimated from the proportion of TP and TN in all evaluated cases. Mathematically, accuracy can be calculated by, Accuracy = (TN + TP)/ (TN+TP+FN+FP) (10) When accuracy of all 3 subjects is compared with the two different algorithms, FWISVM outperforms the existing SVM in all the 3 cases. The result shows that the FWISVM gives the highest overall accuracy.…”
Section: Segmentation Efficiencymentioning
confidence: 99%
“…Various automated techniques using atlas-based or deep-learning (DL) techniques have been developed to overcome these problems. Although automated image segmentation models for the brain show limitations [15,16], FreeSurfer (FS) [17] can extract brain structures with relatively high accuracy. Therefore, FS has been widely adopted as a non-DL automated segmentation method [17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…An automated model for fast segmentation and diagnosis without involving intricate methods should be developed for clinical use. Although DL segmentation has been used in various fields, including medicine [16], the segmentation of brain structures in MRI for the diagnosis of neurodegenerative diseases has made little progress. In addition, no study has introduced artificial-intelligence-based analysis or demonstrated the usefulness of DL (i.e., complexity or disease discrimination performance) compared with existing non-DL automated segmentation of brain structures (e.g., FS).…”
Section: Introductionmentioning
confidence: 99%
“…Images produced in such an environment display a restricted range of gray-level distribution and lower intensity frequencies, leading to intensity inhomogeneity, low contrast, and low-quality images [1]. Non-uniform gray-level distribution and low contrast may degrade the performance of subsequent image processing, such as image segmentation [2]. Enhancing image intensity boosts information richness in images, particularly in terms of edges, information, contrast, and regions boundaries, which facilitate human visual perception and computerized image analysis [3].…”
Section: Introductionmentioning
confidence: 99%